A review of the genus Hoplocheiloma Cresson (Diptera: Micropezidae) - Marshall, S. A. (Zootaxa, 2011)
The Caribbean genus Hoplocheiloma, which contains eight known species, is reviewed with the redescription of all named species and the description of the following new species: H. rhytisma, H. dominica, H. jamaica and H. hispaniola. Hoplocheiloma notitipenne Cresson is synonymized with H. maculosum (Loew), H. fabricii Steyskal is synonymized with H. totliana (Gmelin), and Gymnosphen macropyga Frey is transferred from Hoplocheiloma to Calosphen. All Hoplocheiloma species are keyed and illustrated.